Fulgencio Batista : from revolutionary to strongman - Argote-Freyre, Frank (New Brunswick, N.J. : Rutgers University Press, 2006)
Second only to Fidel Castro, Fulgencio Batista is the most controversial leader in modern Cuban history. And yet, until now, there has been no objective biography written about him. In this book, the first of two volumes, Frank Argote-Freyre provides a full and balanced portrait of this historically shadowed figure. Drawing on an extensive review of Cuban newspapers, government records, memos, oral history interviews, and a selection of Batista's personal documents, Argote-Freyre moves beyond simplistic caricatures to uncover the real man-one with strengths and weak.
Frontmatter -- Contents -- Preface -- Acknowledgments -- Chapter 1. End and Beginning -- Chapter 2. Restless Adolescence -- Chapter 3. Sergeant Stenographer -- Chapter 4. Machadato -- Chapter 5. Sergeants' Revolt -- Chapter 6. Revolution of 1933 -- Chapter 7. An End to Revolution -- Chapter 8. The Mendieta Years -- Chapter 9. Labor Unrest -- Chapter 10. The Elections of 1936 -- Chapter 11. In the Shadow of Batista -- Chapter 12. Cuban Strongman -- Chapter 13. Road to Democracy -- Notes -- Bibliography -- Index -- About the Author
Includes bibliographical references (pages 275-375) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Batista y Zaldívar, Fulgencio, -- 1901-1973.; Batista y Zaldívar, Fulgencio, -- 1901-1973; Cuba -- History -- 1933-1959.; Presidents -- Cuba -- Biography; Cuba -- Histoire -- 1933-1959.; Présidents -- Cuba -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies; Presidents; Cuba; 1933-1959; History; Biographies